2017
DOI: 10.1007/s10612-017-9359-6
|View full text |Cite
|
Sign up to set email alerts
|

The Neglect of Quantitative Research in Green Criminology and Its Consequences

Abstract: While interest in green criminology has rapidly expanded over the past twenty-five years, much of this growth has occurred on the periphery of orthodox criminology. This article suggests that green criminology's marginalization is partially a result of its non-quantitative methodology. We hypothesize that non-quantitative tendencies within green criminology distance it from orthodox criminology because orthodox criminology values quantitative methods. Here, we examine how neglecting quantitative research metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 64 publications
0
44
0
2
Order By: Relevance
“…To conclude, by exploring the relational character of green criminal violations throughout the United States, this geospatial study of EPA ECHO data has aided in bridging the research gap identified by Lynch et al. (). In doing so, we have introduced the concept of green crime havens as an analytical tool for describing issues of environmental injustice as they intersect with green criminal enforcement.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To conclude, by exploring the relational character of green criminal violations throughout the United States, this geospatial study of EPA ECHO data has aided in bridging the research gap identified by Lynch et al. (). In doing so, we have introduced the concept of green crime havens as an analytical tool for describing issues of environmental injustice as they intersect with green criminal enforcement.…”
Section: Discussionmentioning
confidence: 94%
“…Despite their frequency and serious consequences, the geography of green crimes throughout the United States has not been extensively examined from a criminological perspective. Green criminology has relied more on descriptive case studies and underutilized quantitative methods traditionally associated with orthodox criminology (Lynch et al., ). The need for more quantitative analysis assessing different theoretical hypotheses from a green criminological perspective is immediately evident.…”
Section: Green Crime Havensmentioning
confidence: 99%
“…'Offenders' stories are taken as devices meant for manipulation ', Presser (2016: 146) contends, and, as such, 'a perspective tied too closely to their stories would likely seem suspect'. Another reason may be that mainstream or 'orthodox' criminology, as it is sometimes called, privileges quantitative research methods (Lynch et al 2017), dismissing the 'narrative data that are everywhere around us in the buildup to and aftermath of crimes' (Maruna 2015: ix). 4 Following Presser (2010: 432), Presser and Sandberg (2015: 16n.1), and Sandberg and Tutenges (2015: 158)-and in an effort to maintain consistency with my prior work-I use the terms 'narrative' and 'story' interchangeably.…”
Section: Resultsmentioning
confidence: 99%
“…Much less attention has been given to the other stages related to the crime commission process, for example where poachers decide to enter or exit a protected area and why those specific locations were chosen. In the last decade, criminologists have also started to study wildlife poaching, mainly with qualitative, descriptive, conceptual, or exploratory research designs (Lynch et al 2017). Recent reviews show that quantitative studies on the decisionmaking of poachers and rangers are missing from the literature Lynch et al 2017;McFann and Pires 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, criminologists have also started to study wildlife poaching, mainly with qualitative, descriptive, conceptual, or exploratory research designs (Lynch et al 2017). Recent reviews show that quantitative studies on the decisionmaking of poachers and rangers are missing from the literature Lynch et al 2017;McFann and Pires 2020). Hence, here lies an opportunity to apply a criminological perspective outside of its traditional urban setting and advance current wildlife poaching research.…”
Section: Introductionmentioning
confidence: 99%